Pharmacoeconomics In India: The Need for Cost-Effectiveness in Drug Therapy - Akash Jain (Innovations in Pharmacy Planet, 2016)
Pharmacoeconomics plays a crucial role in optimizing healthcare expenditures while ensuring effective drug therapy, particularly in resource-limited settings like India. With the rising burden of chronic diseases and increasing drug costs, the need for cost-effectiveness in pharmacotherapy has become more significant. This review explores the principles of pharmacoeconomic, including cost-effectiveness analysis, cost-benefit analysis, and cost-utility analysis, and their relevance in the Indian healthcare system. The disparities between public and private healthcare, the impact of branded versus generic drugs, and the role of government policies such as the Drug Price Control Order (DPCO) are discussed in detail. Despite efforts to regulate drug pricing, challenges such as limited pharmacoeconomic research, lack of standardized health data, and physician and patient resistance hinder the effective implementation of cost-effective prescribing. Recent advancements, including Health Technology Assessment (HTA) and digital tools, offer promising solutions to enhance cost-efficiency in drug therapy. Strengthening pharmacoeconomic policies and promoting awareness among stakeholders is crucial for ensuring equitable access to affordable and effective medications in India. This review highlights the urgent need for integrating pharmacoeconomic principles into healthcare decision-making to improve patient outcomes while optimizing resource allocation.